2022
DOI: 10.1093/cid/ciac282
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance and Correlation of Severe Acute Respiratory Syndrome Coronavirus 2 Viral RNA, Antigen, Virus Isolation, and Self-Reported Symptoms in a Longitudinal Study With Daily Sampling

Abstract: The novel coronavirus pandemic incited unprecedented demand for assays that detect viral nucleic acids, viral proteins, and corresponding antibodies. The 320 molecular diagnostics in receipt of FDA emergency use authorization mainly focus on viral detection; however, no currently approved test can be used to infer infectiousness, i.e., the presence of replicable virus. As the number of tests conducted increased, persistent SARS-CoV-2 RNA positivity by RT-PCR in some individuals led to concerns over quarantine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Some studies found that detection of sgRNA correlates with detection of infectious virus 4,173,174 , and that sgRNA was rarely detectable 8 dpos 67 . However, sgRNA was detected in diagnostic samples up to 17 days after initial detection of infection 175 or in culture-negative samples 176 , probably owing to the stability and nuclease resistance of double-membrane vesicles containing sgRNAs. Thus, although the absence of sgRNA would indicate absence of viral replication, the presence of sgRNA does not necessarily indicate infectiousness 19 .…”
Section: Sars-cov-2 Diagnostics In Public Healthmentioning
confidence: 99%
“…Some studies found that detection of sgRNA correlates with detection of infectious virus 4,173,174 , and that sgRNA was rarely detectable 8 dpos 67 . However, sgRNA was detected in diagnostic samples up to 17 days after initial detection of infection 175 or in culture-negative samples 176 , probably owing to the stability and nuclease resistance of double-membrane vesicles containing sgRNAs. Thus, although the absence of sgRNA would indicate absence of viral replication, the presence of sgRNA does not necessarily indicate infectiousness 19 .…”
Section: Sars-cov-2 Diagnostics In Public Healthmentioning
confidence: 99%
“…Abundance of sgRNA among SARS-CoV-2 variants is consistently predicted by levels of genomic RNA when compared to ancestral strains with D614G. Whereas previous studies of sgRNA either predated the widespread emergence of variants of concern or were not designed to compare sgRNA levels between variants [ 2 , 5 , 6 , 11 ], the current study included acute-phase samples of SARS-CoV-2 variants of concern collected across varied patient populations using different swab types. In our analysis, Delta variant samples demonstrated lower sgRNA Ct values (higher levels of sgRNA) than predicted by N2 Ct alone.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to total viral RNA, sgRNA detection demonstrates improved correlation with isolation of live virus and antigen detection, providing a potential indicator of infectivity detectable in the diagnostic clinical sample [ 2 , 5–7 ]. However, the abundance of sgRNA during infections with SARS-CoV-2 variants compared to ancestral strains is relatively unknown.…”
mentioning
confidence: 99%
“…Data in longitudinal studies that captured viral load measurements from early in the course of infection 31,41,43,[47][48][49][50][51][52][53][54][55][56][57][58] present evidence that challenge the assumption that Ag-RDTs will reliably detect pre-infectious and infectious individuals. Viralload timecourses from individuals in these studies show that for some individuals, several days can pass between when viral loads reach potentially infectious levels and when viral loads rise to the limits of detection (LODs) of Ag-RDTs (approximately 10 5 to 10 7 copies/mL).…”
Section: Introductionmentioning
confidence: 99%
“…Although many Ag-RDT evaluations have observed relatively high concordance between Ag-RDT results and infectiousness (as established directly by viral culture 21,34,41,46,[48][49][50][63][64][65][66][67][68][69][70] or presumed by quantitative viral loads or semiquantitative Ct values 22,[71][72][73] ), this high concordance may not hold when Ag-RDTs are used for screening testing in the community. For example, in several studies 34,46,48,64,68,[70][71][72][73] most infected participants were already symptomatic by the time sampling began, so Ag-RDT performance would not be generalizable to the early period of infection.…”
Section: Introductionmentioning
confidence: 99%